UJI EFEKTIVITAS ANTIJAMUR EKSTRAK KULIT JERUK NIPIS (CITRUS AURANTIFOLIA) TERHADAP PERTUMBUHAN TRICHOPHYTON RUBRUM SECARA IN VITRO - Dermawan Cappala Bakurru, (2021)
Indonesia's tropical climate supports the growth of fungi that could attack the skin layer from stratum corneum to stratum basalis, hair and nails that are common in society. This disease is caused by dermatophyte fungi from the genus Trichophyton, Microsporum and Epidermophyton. Trichophyton rubrum is the most common fungal dermatophyte and it is known to cause 60% of all dermatophyte infections. Lime (Citrus aurantifolia) is a plant widely grown in the community and its peel contains various chemical compounds, including flavonoid that have anti fungi functions. This study aims to determine the effectiveness of lime peel extract (Citrus aurantifolia) on the growth of Trichophyton rubrum. This study is an experimental research study that uses a post-test-only control group research design where there are a few concentration groups, 5%, 10%, 25%, 50% and ketoconazole as positive control. This study uses one way ANOVA and post hoc bonferoni statistical test. The results showed that there were effects of lime peel extract (Citrus aurantifolia) on Tricophyton rubrum with the One Way ANOVA test resulted in a p value of 0.001 (p <0.05) and the post hoc bonferoni test showed p < 0.05 in almost every group, which means that there were meaningful differences. Flavonoid is a chemical compound in lime peel extract (Citrus aurantifolia) that has antifungal effectiveness in inhibiting the growth of Trichophyton rubrum by in vitro inhibition of cell wall synthesis, cell division, and synthesis of RNA and protein by the well diffusion method.